1993
DOI: 10.1073/pnas.90.18.8362
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine binding to the Tetrahymena ribozyme: thermodynamic coupling with oligonucleotide binding.

Abstract: The L-21 Sca I ribozyme derived from the group I intron of Tetrahymena thrmophila pre-rRNA catalyzes an endonucease reaction analogous to the first step of selfspicing. Guanosine (G) The 413-base intron of Tetrahymena thermophila nuclear pre-rRNA splices in the absence of protein (1, 2). In the first of two transphosphoesterification steps, exogenous guanosine (G) or one of its 5' phosphorylated forms binds to the intron and attacks at the 5' splice site. The products of the first step are the 5' exon ending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
184
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(212 citation statements)
references
References 22 publications
27
184
1
Order By: Relevance
“…kf was measured side-by-side with E G414 in this study; the value agrees well with the literature values of kf ) 0.55 min -1 (pH 7.0; McConnell et al, 1993) and 0.29 min -1 (pH 6.6; Knitt et al, 1994). kr and k off P could not be determined, as the weak binding of GA5 to the ribozyme prevents saturation from being achieved (T. S. McConnell, D. Herschlag, and T. R. Cech, unpublished results).…”
Section: Observation Of An Internal Equilibrium For the L-21g414 Ribosupporting
confidence: 77%
See 1 more Smart Citation
“…kf was measured side-by-side with E G414 in this study; the value agrees well with the literature values of kf ) 0.55 min -1 (pH 7.0; McConnell et al, 1993) and 0.29 min -1 (pH 6.6; Knitt et al, 1994). kr and k off P could not be determined, as the weak binding of GA5 to the ribozyme prevents saturation from being achieved (T. S. McConnell, D. Herschlag, and T. R. Cech, unpublished results).…”
Section: Observation Of An Internal Equilibrium For the L-21g414 Ribosupporting
confidence: 77%
“…The rate constants were obtained as follows: k on S , from Herschlag et al (1993b); k off S , from the value of 1 min -1 for dissociation of -1d,rS from E ScaI (Herschlag et al, 1993b); this value was corrected by 5-fold to account for the slower dissociation of S in the presence of bound G (McConnell et al, 1993). kf was measured side-by-side with E G414 in this study; the value agrees well with the literature values of kf ) 0.55 min -1 (pH 7.0; McConnell et al, 1993) and 0.29 min -1 (pH 6.6; Knitt et al, 1994).…”
Section: Observation Of An Internal Equilibrium For the L-21g414 Ribomentioning
confidence: 99%
“…The similar rate constants suggest that the constraint on the helical conformation by the extended P1 duplex has at most a small effect on adoption of the transition state structure. This effect could be small because the transition state conformation can be reached within the helix or because the extended P1 duplex is not highly constrained due to the limited stacking following the G•U wobble pair at the cleavage site.Cooperativity in Binding of Reactants-Previous work with the L-21 ScaI ribozyme showed that binding of S strengthened binding of G (or UCG) and vice versa (5,23,28). This thermodynamic coupling of substrates is also observed for the L-16 ScaI ribozyme with CCUCdTA or CCUCdTAAACC bound ( Figure 2C&D).…”
supporting
confidence: 54%
“…A substrate with a 2′-deoxyribose residue at position -1 was used in these experiments to ensure that the chemical step was rate-limiting (23,57). The observed rate constant for cleavage of *S was plotted as a function of G (or UCG) concentration and fit to Eq.…”
Section: Measurement Of Affinities For G and Gaaacc-analogsmentioning
confidence: 99%
See 1 more Smart Citation